Laqab and Kunyah from The Living Sunnah Theory: Study of Makassar Tribe Family in South Sulawesi - Yahya, Muhammad (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
Surnames or aliases are associated with families belonging to the Makassar Tribe in South Sulawesi. In contrast to the formal name documented in the official records, this secondary name or title holds a deeper significance and is more commonly used within the daily lives of Muslim households belonging to the Makassar tribe. The alias is bestowed upon the child throughout their adolescent years by the parents themselves, as a means of honoring their child. The second name is an honorific title within the family. Assigning a secondary name or title is also considered significant in accordance with the tradition/sunnah of the Prophet Muhammad PBUH, who bestowed secondary names onto his followers. Bestowing a specific or honorific title, in addition to demonstrating respect and gratitude towards the recipient, also serves to prevent mistakes in addressing and comprehending individuals in daily interactions. In the era of the Prophet, the designations of laqab and kunyah were bestowed upon individuals to symbolize the Prophet's intimate bond with his companions, expressing both familiarity and reverence. The necessity of scrutinizing the naqd sanad hadith, laqab, and kunyah is crucial in the process of recognizing and differentiating individuals who possess specific names. This is because many companions share common names derived from Asmaul Husna, such as Abdullah, Abdurrahman, Abdurrahim, and others. In order to recognize and establish closer relationships with his companions, he was bestowed with distinct titles that reflected their individual qualities, circumstances, and temperament. Within Makassar tribal families, it is customary for the community to bestow individuals with laqab and kunyah titles as well. The living sunnahhypothesis refers to the practice of the living sunnah within Makassar tribal households, who deeply embrace the Islamic beliefs